Evaluation of Active and Passive Fire Protection Systems and Life-Saving Facilities in the Jakarta Provincial Health Office Building - Hi. Sarmin, Fitrianisa; Setianingsih, Ajeng; Rafida, Neni Herlina (Jurnal Kesehatan Masyarakat Perkotaan, 2025)
Fire is a disaster with a high risk of causing casualties and material losses. World Fire is a disaster with a high risk of causing loss of life and material loss. World Fire Statistics (2022) data recorded more than 3.7 million global fires with losses of approximately USD 50 billion per year. Meanwhile, in Indonesia, there were 10,000 cases in 2021 and 1,624 cases in DKI Jakarta in 2022. This condition emphasizes the importance of fire protection systems in public facilities, including the DKI Jakarta Provincial Health Office Building. This study aims to evaluate active and passive fire protection systems, and life-saving facilities based on Ministerial Regulation No. 26 of 2008 and SNI. The method used was descriptive qualitative with observation, interviews, and document review. The results showed that the fire protection system was in place but not functioning optimally. Active protection was ineffective due to damage to the MCFA, which resulted in the inoperability of alarms, detectors, sprinklers, and hydrants. While fire extinguishers functioned but did not meet placement standards. Passive protection was generally appropriate, but there were deficiencies such as materials and partitions that were not certified fire-resistant, cracks in walls, and fire doors without smoke seals. Lifesaving facilities are relatively up to standard, although evacuation routes remain obstructed, emergency exits difficult to use, assembly points unsafe, and lighting and evacuation signs inadequate. Repairs, maintenance, and regular monitoring are recommended to ensure the safety of building occupants.